Psychological and social effects of COVID-19: investigating task setbacks, burnout, withdrawal behaviour, and perceived organisational support among telework employees in Malaysia - Mustafa, Siti Nur Musfirah; Mohd Mahudin, Nor Diana (Institut Sosial Malaysia (ISM), 2021)
Task setbacks arising from the COVID-19 pandemic and organisational support for teleworkers are newly emerging phenomena affecting the world of work and the workforce; thus, research on these phenomena is scarce. The switch from the conventional working mode to teleworking necessitates investigating it in relation to burnout and work withdrawal behaviour. Focusing on employees in Malaysia, the present study investigated how COVID-19 task setbacks, burnout, withdrawal behaviour, and organisational support interplay in impacting the well-being of teleworkers. Data were collected through a survey from 157 employees who were teleworking full-time due to the movement restrictions. The study found that while COVID-19 task setbacks did not predict employees’ burnout, the latter was positively related to, and predictive of, work withdrawal behaviour. Employees’ burnout was also negatively associated with perceived organisational support for telework tasks. Contrary to the hypothesis, perceived organisational support did not significantly buffer the relationship between burnout and work withdrawal behaviour. Implications for future research, practical interventions, and potential work policy changes based on these findings were discussed.